An overview of peanut and its wild relatives - Bertioli, David J. (2011)
The legume Arachis hypogaea, commonly known as peanut or groundnut, is a very important food crop throughout the tropics and sub-tropics. The genus is endemic to South America being mostly associated with the savannah-like Cerrado. All species in the genus are unusual among legumes in that they produce their fruit below the ground. This profoundly influences their biology and natural distributions. The species occur in diverse habitats including grasslands, open patches of forest and even in temporarily flooded areas. Based on a number of criteria, including morphology and sexual compatibilities, the 80 described species are arranged in nine infrageneric taxonomic sections. While most wild species are diploid, cultivated peanut is a tetraploid. It is of recent origin and has an AABB-type genome. The most probable ancestral species are Arachis duranensis and Arachis ipae¨nsis, which contributed the A and B genome components, respectively. Although cultivated peanut is tetraploid, genetically it behaves as a diploid, the A and B chromosomes only rarely pairing during meiosis. Although morphologically variable, cultivated peanut has a very narrow genetic base. For some traits, such as disease and pest resistance, this has been a fundamental limitation to crop improvement using only cultivated germplasm. Transfer of some wild resistance genes to cultivated peanut has been achieved, for instance, the gene for resistance to root-knot nematode. However, a wider use of wild species in breeding has been hampered by ploidy and sexual incompatibility barriers, by linkage drag, and historically, by a lack of the tools needed to conveniently confirm hybrid identities and track introgressed chromosomal segments. In recent years, improved knowledge of species relationships has been gained by more detailed cytogenetic studies and molecular phylogenies. This knowledge, together with new tools for genetic and genomic analysis, will help in the more efficient use of peanut’s genetic resources in crop improvement.